Etika Pragmatis Jhon Dewey dan Relevansinya Terhadap Pelaksanaan Pembelajaran Daring di Indonesia - Fatimah, Fatimah (Universitas Islam Negeri Imam Bonjol Padang, 2021)
As creatures who have reason and mind, human life cannot be separated from the assessment of good and bad deeds. This is where the position of ethics is so important for the way or direction of human life. With reason, humans can position themselves to act. What to do and what to avoid and leave in accordance with the existing rules. Ethics as a branch of science from philosophy has received very good attention from philosophers. So that from the thinking of these philosophers emerged various types of ethics, one of which is the flow of pragmatic ethics. This pragmatic flow is found in England and America. One of the most influential pragmatists of his time was the pragmatism of John Dewey. The purpose of this study is to find out and describe how John Dewey's pragmatic ethical thinking is and how relevant it is to online learning in Indonesia. In line with the objectives, this research uses the type of research library research and uses descriptive analysis method. As the results of his research, John Dewey's pragmatic ethics teaches that something will be good if we can look for goodness that can be used and not just talk. An important point of John Dewey's teaching of pragmatic ethics is that experience is knowledge applied in practice. A truth will be seen in testing by experiences in practice. An action taken can be considered ethical if it brings a scientific benefit such as producing pleasure, satisfaction and goodness for society. Dewey strongly supports social life and does not like people who live individualistically. For him, a person will have meaning if they can blend in with society because humans cannot live alone and are very dependent on other people. If one lives without society, then one's life is meaningless (sociality education). John Dewey's ethics are closely related to life in today's modern era. The impact of the corona virus requires education in Indonesia to be carried out online or online. Thus, this implementation is related to John Dewey's pragmatic ethics which judges something good based on the practical benefits of a theory or the existence of proof of a theory.